Method for Testing of Drugs Belonging to Substrates and Inhibitors of the Transporter Protein BCRP on Caco-2 Cells - Yu. S. Tranova; A. A. Slepnev; I. V. Chernykh; A. V. Shchulkin; P. Yu. Mylnikov; N. M. Popova; M. I. Povetko; E. N. Yakusheva (Разработка и регистрация лекарственных средств, 2023)
Introduction. Breast cancer resistance protein (BCRP) is an efflux membrane transporter that controls the pharmacokinetics of a large number of drugs. Its activity may change when taking some endo- and exogenous substances, thus making it a link in drug interactions.Aim. The aim of the study was to develop a method for testing of drugs for belonging to BCRP substrates and inhibitors in vitro.Materials and methods. The work was performed on Caco-2 cells overexpressing BCRP, the cultivation was performed in a transwell-system consisting of the apical and basolateral chambers. Cells were seeded at the bottom of the apical chamber, which is a semipermeable membrane. Primarily, the transport of BCRP substrates: methotrexate, mitoxantrone and quercetin was evaluated in the concentration range of 1, 5, 10, and 50 μM in the direction from the basal chamber to the apical one (Papp b-a) and in the opposite direction (Papp a-b). The ratio Papp b-a / Papp a-b more than «2» characterizes the participation of transporter proteins in the transcellular transport of substances. To confirm the participation of BCRP in their transport the experiment was carried out with the addition of a transporter inhibitor, reserpine, to the transport medium at a concentration of 50 μM. The concentration of substrates in the chambers was analyzed by HPLC-MS/MS.Results and their discussion. The addition of methotrexate (1 μM), mitoxantrone (1 μM), and quercetin (1–10 μM) to both the apical or basolateral chambers of the transwell-system, their content in the recipient chamber was not detected. When methotrexate concentration became 5 μM the Papp b-a / Papp a-b ratio was 3.38 ± 0.08, which indicates the involvement of transporters in its transfer. The addition of methotrexate to the donor chamber at concentrations of 10 and 50 μM, Papp b-a / Papp a-b decreased to values below «2». At mitoxantrone concentration of 5 μM Papp b-a / Papp a-b was 2.72 ± 0.16. An increase in the concentration to 10 μM led to an increase in Papp b-a / Papp a-b to 6.18 ± 0.08. With a substance content of 50 μM the indicator decreased but remained above the value «2». In the quercetin concentration of 50 microns, Papp b-a / Papp was below "2". Reserpine reduced Papp b-a / Papp a-b of methotrexate by 3.31 times (p = 0.0002), which indicates the elimination of asymmetry in the transport of the substance. At a mitoxantrone concentration of 10 microns, reserpine reduced its Papp b-a / Papp a-b by 3.36 times (p < 0.0001). The results indicate the participation of BCRP in the control of the transfer of both substances through the cellular monolayer.Conclusion. A method of testing drugs belonging to BCRP substrates and inhibitors using methotrexate (5 μM) and mitoxantrone (10 μM) as marker substrates and reserpine (50 μM) as inhibitor was developed and tested on Caco-2 cells.